Flipped classroom in English language teaching: a systematic review - Turan, Zeynep; Akdag-Cimen, Birgul (Computer assisted language learning, 2020)
The aim of this study is to examine the trends and main findings of the studies concerning the flipped classroom method in the field of English language teaching (ELT). For this purpose, databases including Web of Science, Eric, Taylor & Francis and the Educational full text EBSCO were reviewed, and a total of 43 articles were analysed. Systematic review was used as the research methodology. The articles were analysed utilising a content analysis method. The findings of the study revealed that the flipped classroom method in ELT gained popularity among researchers after 2014, and the number of the studies in the field rapidly increased in the last two years (2016-2017). In addition, the most commonly used research methods in flipped classroom in ELT studies were found to be mixed and quantitative methods. In the examined studies, speaking and writing abilities were the most commonly studied language skills. Further analysis revealed challenges, as well as benefits related to the use of the flipped classroom method in English as a foreign language (EFL) classroom. Additionally, in studies reviewed concerning the effectiveness of the flipped classroom methods, the findings mostly pointed to the benefits of the flipped classroom method. On the basis of the review, various suggestions are made for practitioners and future research.